Evaluation of liver disease progression in the German hepatitis C virus (1b)‐contaminated anti‐D cohort at 35 years after infection. Issue 1 (18th November 2013) - Wiese, Manfred; Fischer, Janett; Löbermann, Micha; Göbel, Uwe; Grüngreiff, Kurt; Güthoff, Wolfgang; Kullig, Ulrike; Richter, Franziska; Schiefke, Ingolf; Tenckhoff, Hannelore; Zipprich, Alexander; Berg, Thomas; et al.
<x xml:space="preserve">Abstract</x> The natural course of HCV infection remains controversial. The German HCV (1b)‐contaminated anti‐D cohort provides an ideal population to investigate the natural course of HCV infection in a large, homogenous cohort of young women from the date of HCV inoculation. Our previous follow‐up studies at 20 and 25 years after infection suggested slow fibrosis progression rates in this unique cohort. The aim of our prospective, community‐based, multicenter study was to reevaluate the liver disease progression in 718 patients of the original anti‐D cohort at 35 years after infection. Patients with self‐limited HCV infection (n = 189) were compared to those who failed to eliminate the virus spontaneously (n = 529), comprising patients who were treatment naïve (n = 197) or achieved a sustained virological response (SVR; n = 149), respectively, failed to clear the virus (non‐SVR; n = 183) after antiviral therapy. In the overall cohort, 9.3% of patients showed clinical signs of liver cirrhosis at 35 years after infection. Liver disease progression largely depended on HCV infection status. The highest proportion of patients with clinical signs of end‐stage liver disease was observed in the non‐SVR group (15.3%), whereas decreased cirrhosis rates were detected in the SVR group (6%) and in patients with self‐limited HCV infection (1.1%; P = 6.2 × 10−6). Overall survival was significantly enhanced after SVR, compared to treatment‐naïve patients or non‐SVR (P = 0.027). Conclusion: The present study provides further evidence for a mild, but significant, disease progression at 35 years after infection in the German HCV (1b)‐contaminated anti‐D cohort. Patients with self‐limited HCV infection or SVR after antiviral treatment were protected from progressive liver disease and showed the best clinical long‐term outcome. (Hepatology 2014;58:49–57)